Interactive Video-Based Experiential Learning for Junior High School StudentsÔÇÖ Understanding of Salat - Afifah, Nabila; Nurdin, Nurdin; Mustafa, Mustafa (Journal of Islamic Education Students (JIES), 2025)
This study aims to improve students' understanding of salat material through the implementation of the Experiential Learning model based on interactive video. The research employed a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The subjects were 26 seventh-grade students of class VII D in the 2024/2025 academic year. Data were collected through observation, written tests, and documentation, using instruments such as lesson implementation observation sheets, student activity sheets, and comprehension tests. Results showed an increase in lesson implementation scores from an average of 40.33 (good) to 47 (very good), student activity from 42.33 (fair) to 52.5 (very good), and understanding of salat from an average score of 75.53 (46.15% mastery) to 89.5 (100% mastery). The improvement in student comprehension reached 53.85%. These findings demonstrate that the interactive video-based Experiential Learning model is effective in enhancing the quality of Islamic Religious Education.┬á┬á